2017
DOI: 10.1038/ncomms16082
|View full text |Cite
|
Sign up to set email alerts
|

Ancient European dog genomes reveal continuity since the Early Neolithic

Abstract: Europe has played a major role in dog evolution, harbouring the oldest uncontested Palaeolithic remains and having been the centre of modern dog breed creation. Here we sequence the genomes of an Early and End Neolithic dog from Germany, including a sample associated with an early European farming community. Both dogs demonstrate continuity with each other and predominantly share ancestry with modern European dogs, contradicting a previously suggested Late Neolithic population replacement. We find no genetic e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
180
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(191 citation statements)
references
References 54 publications
4
180
1
6
Order By: Relevance
“…We generated the whole-genome sequences of two Iberian wolves: one from a captive breeding population belonging to the European Endangered Species Programmes (EEP, henceforth labelled wEEP) and one from southern Spain (Sierra Morena, wSierraMorena). The captive wolf sample consisted of whole blood drawn during a routine veterinary examination from a captive-born wolf at the Zoological Park of Barcelona that descends from the Iberian northwestern population and the sequence obtained for this individual was used in parallel in another study (Botigué et al, 2017). Previous genetic analyses revealed that most of the diversity present in the wild wolf population was also present in the captive population due to the large number of founders used (Ramirez et al, 2006).…”
Section: Sampling and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…We generated the whole-genome sequences of two Iberian wolves: one from a captive breeding population belonging to the European Endangered Species Programmes (EEP, henceforth labelled wEEP) and one from southern Spain (Sierra Morena, wSierraMorena). The captive wolf sample consisted of whole blood drawn during a routine veterinary examination from a captive-born wolf at the Zoological Park of Barcelona that descends from the Iberian northwestern population and the sequence obtained for this individual was used in parallel in another study (Botigué et al, 2017). Previous genetic analyses revealed that most of the diversity present in the wild wolf population was also present in the captive population due to the large number of founders used (Ramirez et al, 2006).…”
Section: Sampling and Sequencingmentioning
confidence: 99%
“…Other samples are available in the NCBI SRA database under the Accession Nos. SRP073312 (Botigué et al, 2017), SRA068869 (Wang et al, 2013), SRP044399 (Fan et al, 2016) and PRJNA274504 (Freedman et al, 2014). Genotypes for the 48K data set (Boyko et al, 2010;vonHoldt et al, 2010vonHoldt et al, , 2011 were provided by Adam Boyko.…”
Section: Data Accessibili Tymentioning
confidence: 99%
“…Over 400 breeds have been described that can be regarded as island-like (closed) populations. Dogs diverged from ancient wolves about 16,000-32,000 years ago (Botigue et al, 2017;Frantz et al, 2016;Thalmann et al, 2013). Recent dog breeds have developed mainly during the past few hundred years through a variety of mechanisms owing to artificial selection, geographic separation, migration and crosses among breeds, giving rise to a remarkable among-breed variation in multiple aspects of morphology and behaviour (Parker et al, 2004;Spady & Ostrander, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although domestication is unlikely to have protected the dogs from contact with dangerous snakes, the process of domestication may have somehow interfered with dogs' interpretation of snake‐related cues. On the other hand, it might be that the populations of gray wolves from which domestic dogs rather recently evolved (Botigué et al, ) were not subjected to significant snake‐related selection pressures in their cold, northerly habitats (Mulholland et al, ). There is likely to be learning involved in recognition of the danger communicated by aposematic signals (Bates & Fenton, ), including rattling, but the two dogs in our sample who were reported to have had direct experience with rattlesnakes readily approached the speakers that were projecting the recorded rattles.…”
Section: Discussionmentioning
confidence: 99%